The Detailed Spatial Planning Policy Formulation and Zoning Regulations In The City Of Yogyakarta - Muhammad Dimas Rizqi; Hartawan Hartawan (Universitas Islam Darul Ulum Lamongan, 2023)
The detailed spatial planning policy formulation and zoning regulations in the city of Yogyakarta are in accordance with the policy formulation process. In the implementation process, there are several stages, namely: First, policy formulation is a process to understand problems or assumptions, diagnose causes, map goals and unify different views, the two policy agendas are a process after policy formulation with policy making that has entered In the policy agenda process, the three choices of alternative policies to solve a problem are to solve a problem, the fourth policy setting is a process to establish policies or endorsements so that there is a binding legal force. The factors that influence are (1) Political factors (2) Economic (financial) factors (3) Administrative factors (Organizational) (4) Technological factors (5) Social and cultural factors (6) Defense and security factors. In the policy formulation process for Detailed Spatial Planning and Zoning Regulations in the City of Yogyakarta, cooperation with various related parties, such as from the private sector, spatial planning experts, academics, and other involved parties, is necessary. In addition, in the implementation process, there must be socialization to the community, a form of socialization such as deliberation (two-way communication), so that there is no friction against the community or related parties. Furthermore, in explaining the zoning regulations, it must be in accordance with the designated zone and pay attention to several aspects such as accuracy, land suitability, and other supporting aspects.